Precise Point Positioning in the Airborne Mode - El-Mowafy, Ahmed (Military Technical College, Cairo, Egypt, 2011)
The Global Positioning System (GPS) is widely used for positioning in the airborne mode, such as in navigation as a supplementary system and for geo-referencing of cameras in mapping and surveillance by aircrafts and Unmanned Aerial Vehicles (UAV). For real-time applications, the traditional differential positioning method cannot usually be used due to its need for data from a ground reference station that should be located within a short range. However, the Precise Point Positioning (PPP) approach can provide an attractive alternative that is based on processing of un-differenced observations from a single GPS receiver. It employs precise satellite orbits and satellite clock corrections. These data are freely available via the internet from several sources, e.g. the International GNSS Service. This data can also broadcast from satellites, such as the new Japanese satellite system QZSS. The PPP can achieve positioning precision and accuracy at the sub-decimetre level. In this paper, the functional and stochastic mathematical modelling used in PPP is discussed. Results of applying the PPP method in an airborne test using a small fixed-wing aircraft are presented. Although the data were processed in a post-mission mode, the same technique can be applied in real time, if precise orbits and clock corrections are available. To evolute the performance of the PPP approach, a reference trajectory was established by differential positioning of the same GPS observations with data from a ground reference station. The coordinate results from the two approaches, PPP and differential, were compared and statistically evaluated. For the test at hand, positioning accuracy at the cm-to-decimetre was achieved for easting and northing coordinates, and doubles that value for height estimation.